2011
DOI: 10.1007/s10974-011-9253-x
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase inhibition attenuates calcium-induced contraction in β-escin but not Triton X-100 permeabilized rabbit femoral artery

Abstract: K+-depolarization (KCl) of smooth muscle has long been known to cause Ca2+-dependent contraction, but only recently has this G protein-coupled receptor (GPCR)-independent stimulus been associated with rhoA kinase (ROCK)-dependent myosin light chain (MLC) phosphatase inhibition and Ca2+ sensitization. This study examined effects of ROCK inhibition on the concentration-response curves (CRCs) generated in femoral artery by incrementally adding increasing concentrations of KCl to intact tissues, and Ca2+ to tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…At 3 min, phosphorylation of MLC but not CPI‐17 decreased to about 60% of the control at 30 s. MYPT1 phosphorylation at ROCK‐specific Thr853 (Murányi et al 2005) was already high (76 ± 7%) at rest and only slightly increased with time after PE stimulation (Supplemental Fig. S8 D ), suggesting an existence of constitutively active ROCK(s) at rest (Clelland et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…At 3 min, phosphorylation of MLC but not CPI‐17 decreased to about 60% of the control at 30 s. MYPT1 phosphorylation at ROCK‐specific Thr853 (Murányi et al 2005) was already high (76 ± 7%) at rest and only slightly increased with time after PE stimulation (Supplemental Fig. S8 D ), suggesting an existence of constitutively active ROCK(s) at rest (Clelland et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, if A-769662 can cause relaxation by inhibition of ROCK and PKC, then A-769662 would be expected to suppress PE-induced contractions. Likewise, A-769662 would be expected to inhibit Ca 2+ -activated contraction of β-escin-permeabilized VSM because ROCK and PKC inhibitors attenuate this response ( Clelland et al, 2011 ). However, a PE-induced contraction of EA was entirely resistant to A-769662.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when considering MA, no data ( Figures 3D,T , n.d.) was obtained for Ang II and VP CRCs, and mouse MA was used to assess the effect of A-769662 on a U-46619 CRC ( Figure 3P ). Permeabilized tissues were activated by addition of Ca 2+ and GTPγS as described previously ( Clelland et al, 2011 ). Data were reported as active force normalized to F 0 (F/F 0 ), and thus, an F/F 0 value of 1 was equal to the maximum KPSS-induced contraction achieved during the initial determination of L 0 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that Y27632 and other ROCK inhibitors inhibit KCl-induced contraction, Ca 2ϩ influx, and MLC phosphorylation in rat aorta and mesenteric artery (25,97), rat tail artery (58), rabbit femoral artery (13), and porcine airway smooth muscle (34). ROCK is a family of Ca 2ϩ -dependent and Ca 2ϩ -independent isoforms (46,79,91 ] i -dependent contraction mechanisms are likely underestimated, and that, in the absence of these rescue Ca 2ϩ -sensitization pathways, the veins could be even more prone to dilation during pregnancy.…”
Section: Diltiazemmentioning
confidence: 99%